The oracle code : a graphic novel - Nijkamp, Marieke; Preitano, Manuel; Bellaire, Jordie; Cowles, Clayton (Burbank, CA : DC Comics, 2020)
After a gunshot leaves her paralyzed below the waist, Barbara Gordon undergoes physical and mental rehabilitation at the Arkham Center for Independence. She must adapt to a new normal, but she cannot shake the feeling that something is dangerously amiss. Strange sounds escape at night while patients start to go missing. Is this suspicion simply a result of her trauma? Or does Barbara actually hear voices coming from the center's labyrinthine hallways? It's up to her to put the pieces together to solve the mysteries behind the walls. In The Oracle Code, universal truths cannot be escaped, and Barbara Gordon must battle the phantoms of her past before they consume her future. --
Chiefly illustrations.
"DC graphic novels for young adults."--Back cover.
Ages 13+
Grades 10-12
Accelerated Reader
Keywords: Gordon, Barbara -- (Fictitious character) -- Comic books, strips, etc; Hackers -- Comic books, strips, etc; Rehabilitation -- Comic books, strips, etc; Self-actualization (Psychology) -- Comic books, strips, etc; People with disabilities -- Comic books, strips, etc; Physical therapy -- Comic books, strips, etc; Psychotherapy -- Comic books, strips, etc; Young adult fiction; Graphic novels; People with disabilities -- Fiction; Rehabilitation -- Fiction; Self-Actualization (Psychology) -- Fiction; Mystery and detective stories; Pirates informatiques; Roman pour jeunes adultes; YOUNG ADULT FICTION / Comics & Graphic Novels / Coming of Age; YOUNG ADULT FICTION / Comics & Graphic Novels / Superheroes; Gordon, Barbara -- (Fictitious character); Young adult fiction; Psychotherapy; Physical therapy; Hackers; Self-actualization (Psychology); Rehabilitation; People with disabilities; Handicapped teenagers -- Comic books, strips, etc; Rehabilitation -- Comic books, strips, etc; Self-realization -- Comic books, strips, etc; Handicapped -- Fiction; Rehabilitation -- Fiction; Self-realization -- Fiction; Mystery fiction; Comic books, strips, etc; Young adult fiction; Graphic novels; Coming-of-age comics; Young adult works; Psychological comics; Fiction; Comics (Graphic works); Graphic novels; Graphic novels; Coming-of-age comics; Psychological comics; Graphic medicine (Comics)